P232 Too Sweet for Too Long?. (12th November 2015) - Ali, S; Khetan, R; Sachdev, P; Bhatt, J
Abstract : Background: Cystic fibrosis related diabetes (CFRD) is associated with deterioration in clinical status. Lung function and nutritional status deteriorate up to 2–4 years before a diagnosis of CFRD based on the oral glucose tolerance test (OGTT). Timely detection and treatment is crucial. Aims: To evaluate: adherence to CFRD screening guidelines and whether identifying stages of progressive Cystic Fibrosis Insulin Deficiency (CFID) using the extended OGTT altered management trends in weight, BMI and FEV1 in CFRD as compared to CF controls. Methods: Retrospective analysis using patients' records. 7 patients with CFRD were compared to matched CF controls using mean z-scores for weight, BMI and FEV1. Results: Records of 59 children (23 males) were analysed, 21 children between 5–10 years and 38 >10 years. In the younger group, 80% (n = 17) had both HbA1c and random glucose tested as per our guidelines. Of 38 patients aged >10 years, 78% (n = 30) were screened by OGTT of whom 16% (n = 5) had the standard test. Table 1 summarises the results and shows the degree of glucose impairment on OGTT and the related grade of cystic fibrosis insulin deficiency (CFID). The mean weight and BMI z scores for those with CFRD compared to controls were -0.64 vs -0.02(p = 0.005) and -1.26 vs -0.03(P = 0.0001). There was a lower trend in FEV1 in CFRD, 1.87l (73.06%) vs 2.35l (89.03%). 3 patients with CFID3 and 1 with CFID1 later commenced insulin based on clinical grounds. Conclusions: Adherence to screening guidelines needs to be improved. Patients with CFRD have a significant declining trend in weight, BMI and FEV1 compared to controls. Some patients with CFID were commenced insulin on clinical grounds rather than results of extended OGTT. Whether treatment at earlier stages of CFID will slow down the rate of decline needs to be explored, but we have reverted back to the standard OGTT for the present.